Hiring Frictions in a Regulated Occupation: Evidence from US Laboratories. (6th September 2020) - Weaver, Andrew
Abstract: Determining the nature and source of hiring frictions is an important topic for policymakers, as these frictions impact both worker outcomes and economic growth. To date, there has been very little US‐based research that has combined detailed measures of employer skill requirements, market structure, organizational characteristics and hiring difficulties at the establishment level. Prior to this study, there has been almost no research that has investigated these issues in the context of a highly regulated industry such as healthcare, which employs more workers than either retail or manufacturing. Using a unique, nationally representative dataset, this study finds that organizational practices and market structure are more relevant predictors of hiring difficulties for laboratory technologists than factors, such as skill mismatch, that are often assumed to be of primary importance.